Externalizing and Internalizing behavioral problems in Adolescents - Sulejmanovic, Dijana Z. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
Socio-emotional problems and behavioral issues in children and adolescents can pose a risk for the development of more serious disorders later in life. As part of mental health care, it is essential to pay special attention to measuring the overall emotional state and health problems that are becoming increasingly frequent and visible. The prevalence of behavioral problems among youth is a growing concern. These issues are typically categorized into externalizing and internalizing disorders, reflecting the various ways adolescents manifest and cope with internal and external conflicts.The aim of this study was to examine the prevalence of externalizing and internalizing behavioral problems in adolescents, explore potential sociodemographic differences, and investigate the relationship between these two types of behavioral issues. The research applied the YEPS questionnaire to meeasure externalizing problems and the DASS-21 scale to measure internalizing problems. The study sample consisted of 1086 adolescents, aged 14 to 19 years (M = 16.98, SD = 1.58), with the majority being female (678, or 62.4%).The main findings of the study indicate the presence of both externalizing and internalizing behavioral problems among adolescents, with externalizing issues being more prevalent in males and internalizing problems more common in females. The results indicate moderate symptoms of behavioral problems, while statistically significant intercorrelations were found between externalizing and internalizing behavioral problems.
Keywords: adolescents; behavioral problems; externalizing problems; internalizing problems